EFEKTIFITAS CONE AERATOR DAN FILTRASI KULIT KERANG DALAM MENURUNKAN KADAR BESI (Fe) DAN KADAR KEKERUHAN PADA AIR SUMUR GALI - Pradana, Tedy Dian (Jurnal Ilmiah Ilmu Kesehatan: Wawasan Kesehatan, 2019)
In West Kalimantan that the access level of protection of clean water only reached 41% of the target MGD's by45.1%, therefore most people use groundwater for their daily needs. Groundwater is a source for the daily needs of the community in Parit Bugis Gang Mustika 1 Kuburaya district so that people looking for alternative sources of clean water. From the beginning pedahualuan test showed levels of iron (Fe) is 4.36 mg / l and turbidity 58NTU.kandungan appropriate RI Permenkes 416 / Menkes / Per / IX / 1990, concerning water quality standardsare 25 NTU turbidity womb and womb iron (Fe) 1 mg / l. This research aims to reduce the content of turbidity and iron content (Fe). The specific objective Analyzing the difference turbidity content and the content of iron (Fe) before and after and see the use of aerators and filtration Cone shells and look at the effectiveness before and after filtration Cone Aerator and seashells in lowering levels of turbidity and levels of iron (Fe). This study is True Experiment (Experiment Pure) aims to determine the ability of aerators and filtration Cone shells in reducing turbidity and iron (Fe) in water wells. The research sample of 24 samples. The statistical test used was Test T Test. Paired sample test results showed that there were significant differences between the content of turbidity and iron content (Fe) before and after using aerators and filtration cone shells. cone method aerator significant value of0.000 <0.05 and filtration seashells significant value of 0.000 <0.05. Seashells filtration method is more effective in decreasing Fe compared to the cone aerator. , For people in the trenches Bugis alley mustika 1 This method can be used as a water treatment in water wells for maximum results that people can use lime as coagulant dosage in accordance with usage.